Implications for the Ergogenic Benefits of Self-Selected Music in Neurological Conditions: A Theoretical Review - Christopher G. Ballmann; Rebecca R. Rogers; Sophia L. Porrill; Nicholas B. Washmuth (Neurology International, 2025)
The ergogenic effects of music have been well described across various modes of exercise with widespread use across competitive athletes and recreational exercisers alike. Underlying the acute beneficial effects of music during exercise are profound physiological and psychological changes which involve an array of different organ systems, including but not limited to cardiovascular, endocrine, skeletal muscle, and nervous systems. While the use of music to enhance physical performance and improve associated mechanisms has been largely optimized in healthy individuals, the investigations of the translation to individuals with neurological conditions are still ongoing. Recently, it has been established that the personalization of music interventions greatly influences performance-enhancing benefits and aids in physical performance optimization in healthy individuals. Self-selected music (SSM) has been documented to impart ergogenic advantages over pre-determined or non-preferred music, including improved cardiorespiratory endurance, power development, and velocity of movement which are characterized by adaptative physiological and psychological changes. Evidence of the benefits of SSM has progressed to the degree to which the overlap of possible benefits between healthy and clinical populations is becoming more apparent. This aim of this theoretical review is to discuss how personalized music influences psychophysiological determinants of exercise ability in healthy individuals and consider how these findings may be applicable to neurological conditions to enhance exercise capacity. The current knowledge on the role of SSM in augmenting physiological and psychological responses to exercise in healthy individuals is presented along with how these mechanisms might be leveraged to overcome exercise limitations in neurological conditions. Overall, SSM appears to have theoretical support to be a promising therapeutic approach to improving exercise ability in neurological conditions through similar ergogenic mechanisms documented in healthy individuals, but further investigation is warranted.